ERGONOMIC WORK SYSTEM DESIGN USING KANSEI ENGINEERING APPROACH - Hari Purnomo; Vitri Lestari; Alex Kisanjani (SINERGI, 2020)
Work fatigue is a problem that most often arises in the workplace and can affect work productivity. That problem also occurs at PT ASA Yogyakarta, many workers who complain of aches in the upper muscles and waist at work. Based on this, the research aims to design an ergonomic work system on the sewing production floor of PT. ASA Yogyakarta. The design of the work system is done to fix the problems done by workers so that it is expected to increase productivity. The method used is Kansei Engineering. The results of this study indicate that the proposed work system design meets the desires of workers with Stuart-Maxwell values testing marginal homogeneity of Z> 0.05. Work system designs made include sewing chairs and tables adjusted in size to worker anthropometry, approved backrests on chairs, lighting lamps replaced with LED lights, plug lamps on sewing machines, and plug bulkheads as sound dampers.